2011
DOI: 10.3208/sandf.51.835
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Image Analysis Method to Study LNAPL Migration in Porous Media

Abstract: A novel Simpliˆed Image Analysis Method was developed and tested to assess the saturation distribution values for water and LNAPLs (Light Non-Aqueous Phase Liquids) in granular soils subjected to ‰uctuating groundwater conditions. This method, based on the Beer-Lambert Law of transmissivity, determines the saturation of water (Sw) and LNAPLs (So) by comparing the average optical densities (Di) for each matrix element of the tested domain to the corresponding average optical densities for three base pictures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Hence, this method allows for the measurement of the degree of saturation of two fluids in a three-phase system (Flores et al, 2011;Kechavarzi et al, 2005;Kechavarzi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, this method allows for the measurement of the degree of saturation of two fluids in a three-phase system (Flores et al, 2011;Kechavarzi et al, 2005;Kechavarzi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The saturation distributions of water and diesel in the entire flow domain under transient condition are measured by the SIAM (Flores et al, 2011). The two-phase column and Tempe pressure cell data yield soil-liquids characteristic curves (SLCCs) of air/water and air/diesel systems.…”
Section: Discussionmentioning
confidence: 99%
“…The SIAM developed by Flores, Katsumi, Inui, and Kamon (2011) is employed in this research to assess the saturation distributions of water and LNAPL in sand under transient condition. This method is a non-intrusive and non-destructive technique to measure saturations of fluids in porous media in the entire domain of the experimental column.…”
Section: Simplified Image Analysis Methods (Siam)mentioning
confidence: 99%
See 1 more Smart Citation
“…An overview by AGAOGLU et al (2015) found that the laboratory work involved non-destructive and non-intrusive imaging techniques which used characterization and observation of multiphase flow system for greater accuracy. Therefore, a number of researchers (JANINA et al, 2017;SITTHIPHAT & SIAM et al, 2016;PENG et al, 2015;SA'ARI et al, 2015;KAMARUDDIN et al, 2011;NGEIN et al, 2011;FLORES et al, 2011;OOSTROM et al, 2007) have carried out various techniques and methods of non-destructive image analysis for liquid migration experiments. As stated by MAAS & HAMPEL 2006, an image analysis technique in the field of civil engineering was normally used to study the object flow absorption movement in boundary layers and liquid migration of small properties specific to the propagation of structure crack extension, and for this argument, a digital image processing technique was acceptable for use in the study of LNAPL migration in a fractured double-porosity soil.…”
Section: Introductionmentioning
confidence: 99%